Mapping of Thoracodorsal Artery Perforators: Accuracy of Thermography and Handheld Doppler - Illg, Claudius; Heinzel, Johannes C.; Denzinger, Markus; Schäfer, Ruth C.; Daigeler, Adrien; Krauss, Sabrina (Journal of Reconstructive Microsurgery, 2024)
Background The versatile musculocutaneous latissimus dorsi flap and the thoracodorsal artery (TDA) perforator flap have developed into indispensable approaches in reconstructive surgery. While the anatomy of the TDA is consistent, the skin perforators vary in location and course. Dynamic infrared thermography (DIRT) recently gained popularity for perforator identification; however, its use and accuracy in thoracodorsal artery perforator (TDAP) mapping is yet to be determined.Methods TDAPs were visualized in 50 cases by DIRT. Based on the thermographic hotspots, the corresponding perforators were then identified by color duplex ultrasound (CDU) and handheld Doppler in a blinded fashion by two separate examiners.Results The midpoint of all perforator fascia passages was localized 99.7 mm caudal and 13.5 mm medial of the posterior axillary fold. The positive predictive value of perforator identification by dynamic infrared thermography was 86.5% and the correlating perforator fascia passage was 9.9 ± 5.8 mm from the hotspot midpoint, with a maximum of 29 mm. The positive predictive value of perforator identification by handheld Doppler was 95% and the signal was 7.2 ± 5.1 mm from the perforator fascia passage.Conclusion DIRT precisely localizes TDAPs. The fusion with CDU combines both modalities' advantages. The combination with handheld Doppler is a fast way of perforator imaging, decreasing the handheld Dopplers' high false positive rate.
Keywords: thoracodorsal artery flap; latissimus dorsi musculocutaneous flap; thermography; DIRT; color duplex ultrasound; handheld Doppler